2019
DOI: 10.1097/aog.0000000000003264
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Neonatal Resuscitation at 22 Weeks of Gestation

Abstract: To evaluate the cost effectiveness of three different approaches to the care of neonates born at 22 weeks of gestation: universal resuscitation, selective resuscitation, or no resuscitation. METHODS:We constructed a decision-analytic model using TreeAge to compare the outcomes of death and survival with and without neurodevelopmental impairment in a theoretical cohort of 5,176 neonates (an estimate of the annual number of deliveries that occur in the 22nd week of gestation in the United States). We took a soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The answers to the question "How small is too small?" should always change with time and place, according to the medical standard, socioeconomic status, culture of each region, and so on (27)(28)(29)(30)(31)(32). In Japan, an approach of universal resuscitation is favored for neonates at 22 and 23 weeks of gestation, although the definitive criteria on the threshold of birthweight for resuscitation remain unestablished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The answers to the question "How small is too small?" should always change with time and place, according to the medical standard, socioeconomic status, culture of each region, and so on (27)(28)(29)(30)(31)(32). In Japan, an approach of universal resuscitation is favored for neonates at 22 and 23 weeks of gestation, although the definitive criteria on the threshold of birthweight for resuscitation remain unestablished.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the 2010 American Heart Association guidelines on neonatal resuscitation proposed that the threshold for withholding resuscitation might be GA <23 weeks or birthweight <400 g (29)(30)(31). Leah et al reported that neither selective nor universal resuscitation at 22 weeks of gestation is cost-effective compared with no resuscitation (32).…”
Section: Discussionmentioning
confidence: 99%